Comparing the Effect of Kinesiology Taping on Dynamic Balance and Pain of Men and Women With Unilateral Patellofemoral Pain Syndrome - Zeinab Sadat Hosseini; Mohammad Javad Tarrahi; Zohreh Shafizadegan; Javid Mostamand (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: Patellofemoral Pain Syndrome (PFPS) is one of the most common disorders of the knee joint. It is characterized by pain, reduced proprioception, and altered pattern of vastus muscle activation, which effectively maintain the balance needed for performing daily living activities such as walking and running. One treatment method that can reduce pain and improve balance in people with PFPS is Kinesiology Taping (KT). Considering the physiological and anatomical differences in the knee structure of men and women and the importance of studying the effect of KT on the dynamic balance of men with PFPS, this study aims to compare the effect of KT on dynamic balance and pain of men and women with unilateral PFPS. Materials & Methods: This is a quasi-experimental and non-randomized clinical trial. The participants were 30 males and 31 females aged 18-40 years suffering from unilateral PFPS. They were recruited using a convenience sampling method. First, the subjects performed the Y-balance test three times in each of the anterior, posteromedial, and posterolateral directions. The maximum score obtained from the three repetitions in each direction was divided by the limb length and recorded in percentage as a dynamic balance score. After 5 minutes of rest and performing initial tests, the subjects performed the intervention. In this stage, KT with a tension equal to 50%-75% of its initial length was applied on the patella of the involved limb to cause medial glide. The effectiveness of KT was examined under a single-leg squat-test. For this purpose, all subjects performed unilateral squatting on their affected leg for 10 seconds with 45 degrees of knee flexion before and after KT, while their pain level was recorded using the visual analog scale. In case of a 50% reduction in pain, the subjects were allowed to enter the final stage (performing the Y-balance test); otherwise, patellar taping was repeated to obtain the appropriate pain reduction. Results: Within-group comparison of balance parameters before and after KT using the paired t-test showed an increase in the reach distance at three directions in the Y-balance test, revealing a significant improvement in the dynamic balance following KT (P<0.05). According to the independent t-test results, there was no significant difference in balance parameters between males and females before and after the intervention (P>0.05). Moreover, the pain was significantly reduced in both genders after KT (P<0.05), but its difference between men and women was not statistically significant (P>0.05). Conclusion: KT is an appropriate therapeutic intervention for improving dynamic balance and reducing pain in people with PFPS. It seems that KT has the same effect on dynamic balance and pain of women and men with PFPS.